EKSPLORASI ETNOMATEMATIKA PADA LUKISAN KULIT KAYU MASYARAKAT ASEI DISTRIK SENTANI TIMUR - Emanuela Merlin Tandi; Pitriana Tandililing; Mayor M.H. Manurung (FKIP Universitas Cenderawasih, 2022)
Abstract: Ethnomathematical Exploration of the Bark Painting of the Asei Community, East Sentani District. This research is an ethnographic research. The purpose of this study was to explore and analyze the mathematical elements in the Asei community's bark painting which can be used as a source of school mathematics learning. Interviews were conducted with two informants who are “painters” who know and understand the meaning of each painting motif. Collecting data using observation, interviews, documentation and studies literature. The instrument in this study was the researcher himself and the supporting instrument in the form of an interview guide. The results of this study indicate that: (1) the motifs contained in the painting on the bark are: iuwga, khel ea uw, melemay, khaley, mandelauw, yanggunibhi, hiyo-rale, raysim-rale, fouw, isomo, fendei. (2) The mathematical elements contained in the painting motifs are: congruence, rectangle, triangle, kite, rhombus, circle, acute angle, obtuse angle, curved line, reflection, and rotation. Keywords: Ethnomathematics, Bark Painting, Asei Society. Abstrak: Eksplorasi Etnomatematika pada Lukisan Kulit Kayu Masyarakat Asei, Distrik Sentani Timur. Penelitian ini merupakan penelitian kualitatif dengan pendekatan etnografi. Tujuan dari penelitian ini adalah untuk mengeksplorasi dan menganalisis elemen-elemen matematika yang terdapat pada lukisan kulit kayu masyarakat Asei, yang dapat dimanfaatkan sebagai sumber pembelajaran matematika sekolah. Wawancara dilakukan bersama dua orang informan kunci yang merupakan